The history of the ancient world : from the earliest accounts to the fall of Rome - Bauer, Susan Wise (W.W. Norton, 2007)
The first volume in a new series that tells the stories of all peoples, connecting historical events from Europe to the Middle East to the far coast of China, while still giving weight to the characteristics of each country. Historian Bauer provides both sweeping scope and attention to the individual lives that give flesh to abstract assertions about human history. Dozens of maps provide a geography of great events, while timelines give the reader an ongoing sense of the passage of years and cultural interconnection. This narrative history employs the methods of "history from beneath"--Literature, epic traditions, private letters and accounts--to connect kings and leaders with the lives of those they ruled. The result is a tapestry of human behavior from which we may draw conclusions about the direction of world events and the causes behind them.--From publisher description.